Growth and productivity of teak (Tectona grandis) under fertigation through drip irrigation system - MUTANAL, S M; PRABHAKAR, A S (The Indian Journal of Agricultural Sciences, 2014)
A field experiment on productivity of teak (Tectona grandis L.f.) under fertigation was initiated on medium black soils at Teak Farm, Murakatti, Dharwad. under drip irrigated system during 1995. Teak was planted at 2 m apart. The factorial experiment consisted of 3 ferilizer levels, viz D11, 100,21.5 and 83 kg; D2, 200, 44 and 166 kg; D3, 300, 64.5 and 249 kg, N, P and K/ha, and 5 frequencies of fertigation, viz F1, 2; F1, 3; F3 , 4; F4, 6 splits a year; F5 soil application in 2 splits. Height and diameter at breast height were significantly higher with D2 level which were at par with those at D3 leves and higher than Dllevel during the second year of planting. Both basal area and volume were significantly higher at 20, 24, 28 months after planting of teak with D2 and D3 levels compared with D1 level of fertilizer. Fertigation in 6 splits a year recorded higher height, diameter at breast height, basal area and volume than 2 splits of fertigation or soil application. Interaction between fertigation levels and frequency was significant for height at 24 months after planting and diameter at breast height and volume at 28 months after planting of teak. Fertigation of D2 or D3 level in 6 splits a year recorded significantly higher volume than as other treatment combinations.